Daily field checking list by Walter Rosene, April 22, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene, April 22, 1937. Also notes the only food in the Great Horned Owl nest was the head of a female Common Pheasant he also observed several large flocks of female Red-winged Blackbirds. Plustek--flatbed